Pharmacology for Anaesthesia and intensive Care - Peck, T. E. (Cambridge medicine, 2014)
The fourth edition of this market-leading anaesthetic book has been fully updated to include novel oral anticoagulants and neuromuscular reversal agents. Numerous other sections have been expanded or updated to reflect new research and current best practice, and the antibiotics chapter now includes information about commonly encountered pathogens and the drugs used to target them. Basic pharmacological principles, vital to understanding the effects of individual drugs, are dealt with methodically, and the essential physiology is described alongside the relevant pharmacology. This has become the core pharmacology book for the FRCA, covering all the relevant kinetics and dynamics in a compact and easy to navigate format, including clear diagrams and tables. This is an ideal aid to study and practice for junior and trainee anaesthetists. Theatre practitioners, ICU nurses and physicians working in areas that demand a solid foundation of pharmacological knowledge will also find this an invaluable resource.